2012
DOI: 10.1016/j.rpor.2012.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dose distribution in IMRT and RapidArc technique in prostate radiotherapy

Abstract: Analysis presented in this paper, demonstrated that RapidArc can compete with the IMRT technique in the field of treatment plan dosimetry reducing the time required for dose delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 11 publications
1
11
0
1
Order By: Relevance
“…ID is lower for higher energy beams, regardless of the technique (VMAT, IMRT). The results are consistent with the literature, 13 indicating a comparable dose distribution in the dynamic techniques (IMRT and VMAT) in radiotherapy of prostate cancer. Simultaneously Wilcoxon test showed that there is no difference between ID delivered to PTV for VMAT (X-6MV vs. X-20MV; p = 0.53) and for IMRT (6 MV vs. 20 MV; p = 0.2).…”
Section: Irradiation Techniquesupporting
confidence: 91%
“…ID is lower for higher energy beams, regardless of the technique (VMAT, IMRT). The results are consistent with the literature, 13 indicating a comparable dose distribution in the dynamic techniques (IMRT and VMAT) in radiotherapy of prostate cancer. Simultaneously Wilcoxon test showed that there is no difference between ID delivered to PTV for VMAT (X-6MV vs. X-20MV; p = 0.53) and for IMRT (6 MV vs. 20 MV; p = 0.2).…”
Section: Irradiation Techniquesupporting
confidence: 91%
“…The planning is quite simple and straightforward unlike in IMRT which requires multiple runs to achieve an acceptable dose distribution. VMAT is currently evolving as the most popular treatment modality due to shorter time 20 required to deliver treatment as compared to conventional 3D conformal radiotherapy and IMRT technique. This may also reduce a possible uncertainty in dose due to a setup error.…”
Section: Fig 3 -Dose Distribution Of a Unilateral Hip Prosthesis Formentioning
confidence: 99%
“…Irradiation of patients using IMRT, VMAT, CK, and TT techniques is increasingly reported in the literature [16][17][18][19][20][21][22]. Despite the technological differences related to the geometry of generated beams: the changing shape of the beam field vs circular tubes, the dose distributions we obtain as a result of the calculations are very comparable, of course, for "small" cancerous changes.…”
Section: Resultsmentioning
confidence: 79%